The role of brand equity and decoy effect on actual purchase of insulated water flasks - Jhasty Marie Z. Ramizares; Ladine Abygael D. C. David; Phoebe Cates A. Acuesta; Molly B. Mejia; Ardvin Kester S. Ong; John Francis T. Diaz; Pauline C. Dangaran (Cogent Business & Management, 2024)
This study investigated the impact of brand equity and the decoy effect on the purchase of insulated water flasks. This was done in order to address a gap in understanding the decoy effect's effectiveness across sustainable alternatives like insulated water flasks and their influence on consumer purchasing behavior. The research involved 405 participants who completed an internet survey, distributed among different social media platforms. Findings analyzed using higher-order partial least square structural equation modeling with SMART PLS v3.0, revealed that both the marketing mix and the decoy effect significantly influenced actual purchase behavior. Promotion has the most substantial impact within the marketing mix factors while price has the least effect, suggesting that consumers are willing to invest in reusable insulated water flasks due to long-term savings and benefits. Additionally, attitude significantly influences purchasing intentions, highlighting consumers' role in decision-making. The study underscored the importance of individual attitudes and perceived behavioral control in driving purchasing decisions.
Keywords: 650; Brand equity; decoyeffect; insulated waterflask; higher-orderstructural equationmodeling; marketing mix